A tawhidic-linked experience of strategic management from the lessons of hajj pilgrimage - Mhd. Sarif, Suhaimi (Zesdyzar Rokman Resources, 2015)
A Tawhidic-linked experience of strategic management from the lessons of hajj pilgrimage (fifth pillar of Islam) enables the practice of strategic management to be explored from hajj pilgrimage experience as a contingency perspective of strategic management. This study aims to explore the hajj pilgrimage rituals and practices that are based on Tawhidic paradigm to link them theoretically and practically with the strategic management function, concept and process. This study solicited the views of selected hajj pilgrims under the arrangement of establishment (muassasah) for Lembaga Tabung Haji (LTH) on the possible linkage between hajj pilgrimage rituals and strategic management based Tawhidic paradigm through personal interview and observations during the 2013 hajj season. The results of the study suggested that there is some theoretical and practice linkage of Tawhidic paradigm and hajj pilgrimage to strategic management. Given to the nature of hajj service arrangement and the operations (manasik) of hajj, some aspects of hajj pilgrimage rituals and exercises have limited linkages to apply with strategic management. The study is limited to a few hajj experiences on specific hajj season, which may not be conclusive, comprehensive, robust and generalizable. However, the lessons are specific to the hajj contexts only. Future research should get more hajj participants from various hajj seasons with more research instruments.